Universal Human Rights and State Sovereignty - Boiko, Iryna V. (2021)
The relevance of the study is conditioned by the necessity of establishing the degree of interaction of universal rights and freedoms of the individual in civil and international law, as well as the possibility of limiting state sovereignty in the implementation of international obligations to ensure and protect human rights. The purpose of the paper is to investigate the international experience of legal regulation of universal human rights in order to develop ideas for their implementation in the legal framework of countries in transformation, including Ukraine. The leading methods of the study included the analysis of international and European practices of consolidating universal human and civil rights, modelling of legal structures acceptable to Ukraine. As a result of the study, it was concluded that the restriction of state sovereignty is possible only in favour of the individual based on the priority of human rights. The research materials can be useful for lawyers and government officials performing draft law activities, teachers of law schools, as well as officials and public administration officials who seek to apply the standards and practices of international regulation of universal human and civil rights in individual management cases